Ericoid mycorrhizal fungi and potential for inoculation of commercial berry species (Vaccinium corymbosium L.) - Bizabani, Christine (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
Ericaceous plants are the richest growth form of the fynbos vegetation of South Africa. The fynbos is characterized by highly leached acidic soils, low mineral nutrients and climatically it is a winter rainfall and dry summer region. Ericoid mycorrhizal fungi associate with Erica species enhancing their ability to access essential nutrients for survival under unfavourable growth conditions. The aim of this study was to select local Ericaceae plant species and to isolate, identify and characterize the ericoid endophytes and assess these isolates as potential inocula for commercial berry species. Two ericaceous plants Erica cerinthoides L. and Erica demmissa Klotzsch ex Benth. were identified from the Mountain Drive area of Grahamstown, Eastern Cape. Root staining was used to confirm the mycorrhizal status of both plants. Hyphal coils typical of ericoid association were observed within the epidermal cells of the hair roots under a light microscope. The endophytes were successfully isolated in pure culture on 2% malt extract agar (MEA) and modified Fontana medium. Cultural morphology and microscopy were used for initial identification. Two slow growing isolates were selected. These isolates were further subjected to molecular identification; extracted DNA was amplified using ITS1 and ITS4 fungal primers. The rDNA gene internal transcriber spacer (ITS) was then sequenced and analyzed by comparison to sequences in the GenBank. On the basis of percentage sequence identity Lachnum Retz. species and Cadophora Lagerb. & Melin species were identified as the ericoid endophytes of E. cerinthoides and E. demmissa respectively. The optimum growth parameters of the fungal isolates were determined in 2% MEA incubated at varying temperatures and pH. It was established that both species had optimum growth at 27â °C and pH 5. The Ericaceae species are sometimes found in metal contaminated sites were ericoid fungi have been proved to alleviate toxicity of their host. The fungal isolates were grown in increasing concentration of CuÂ²â º and ZnÂ²â º in 2% MEA. The growth of Lachnum species decreased with increasing ZnÂ²â º ions above 2.7 mM while Cadophora species showed a change in morphology and also decreased in growth with increased ion concentration. However there were no significant differences recorded in the growth of Cadophora and Lachnum species on increasing CuÂ²â º concentration. Lachnum and Cadophora isolates were formulated into a semi solid inoculum and inoculated onto micropropagated Vaccinni corymbosum L. plantlets of 5 different varieties. Colonization was low for all varieties, Elliott and Brightwell varieties recorded the highest colonization of 35% and 31% respectively. Lachnum species infected roots showed potential ericoid structures while the Cadophora inoculated plantlets had hyphal coils within the cortical cells typical of ericoid mycorrhizas. Inoculation significantly enhanced the shoot growth of Brightwell and Elliott varieties. The Chandler variety inoculated with Lachnum species showed improved shoot dry weight. The Bluecrop and Elliott varieties inoculated with Cadophora and Lachnum accumulated more root biomass. All inoculated Bluecrop plantlets had an improved canopy growth index. Brightwell plantlets inoculated with Lachnum species also had an enhanced canopy growth index. The growth responses were variable within varieties and between varieties. Treatments with the Cadophora and Lachnum have shown potential in the promotion of growth of the Blueberry species. The findings indicate the need to conduct trials under conditions which simulate the commercial growth conditions so as explore the optimum potential of the isolates.
Keywords: Ericaceae; Mycorrhizas; Fynbos